Health services for sexually transmitted infections: Where are we at in New Zealand? A narrative literature review - Kyle J Wilby; Alesha J Smith (CSIRO Publishing, 2020)
Abstract INTRODUCTIONSexually transmitted infection (STI) rates continue to rise in New Zealand. To effectively prevent, test and diagnose STIs in a timely manner to limit their health effects, health services must be appropriate and accessible for all. AIMThe aim of this review was to identify and collate the existing literature and identify gaps in research relating to STI health service delivery in New Zealand. METHODSA critical narrative literature review was conducted. A keyword search of PubMed (2010 to October 2020), EMBASE (2010 to October 2020) and Google Scholar (2010 to October 2020) was conducted. The electronic search was supplemented with manual screening of references from identified articles. Eligible studies reported on STI service delivery in New Zealand. Articles not meeting these criteria were excluded. Articles solely reporting on the human papillomavirus vaccine or condom use statistics or perceptions were also excluded. Data extracted included study year, authors, aim, methods and outcome results. RESULTSA total of 179 articles were identified, including 16 that met study inclusion criteria. Nine studies focused on STI testing, five on health-seeking behaviours and two had other foci. The results reflected substantial gaps in the funding and delivery of best-practice STI management across all New Zealand. DISCUSSIONNew strategies are needed to improve access to low-cost or free services for sexual health care in general and clinic-wide systems implemented to enable routine delivery of advice about STI prevention and testing by clinicians to patients.